The Role of Leading Sectors and Balancing Funds in Reducing Poverty and Improving the Welfare in the Papuaprovince - Abu Bakar (Dinasti Publisher, 2024)
This research investigates the role of the primary sector and balancing funds in efforts to reduce poverty and enhance the welfare of the population in the Province of Papua, utilizing a panel data analysis approach. The data utilized spanned from 2018 to 2021, encompassing 29 regencies/cities in the Province of Papua. The data were obtained from the Papua Province Central Statistics Agency and the Directorate General of Fiscal Balance, Ministry of Finance of the Republic of Indonesia, which was collected using documentation techniques. The results of our analysis reveal significant findings. First, it was found that leading sectors, general allocation funds and revenue sharing funds have a significant impact in reducing poverty levels in this region. Second, poverty also has a significant influence on the welfare of the population. Furthermore, our research results also show that leading sectors, general allocation funds and revenue sharing funds have a significant impact in improving the welfare of the population directly, but not significantly through poverty.